Implementation of advanced practice nursing for minor orthopedic injuries in the emergency care context: A non-inferiority study. (June 2021) - Boman, Erika; Duvaland, Elisabeth; Gaarde, Kim; Leary, Alison; Rauhala, Auvo; Fagerström, Lisbeth
Abstract: Aims: To evaluate the implementation of advanced practice nursing for patients with minor orthopedic injuries, including comparison of outcomes in relation to advanced practice nurse versus standard (physician-led) care models. Design: A non-inferiority study was performed in an emergency department in Norway, where advanced practice nursing is in an initial stage of implementation. The non-inferiority design was chosen to test whether the new advanced practice nursing model does not compromise quality of care compared to the standard care model already in use. Methods: Patients with minor orthopedic injuries were assessed and treated by either advanced practice nursing or standard (physician-led) care models. Participating patients were assigned to the professional available at presentation. In the nursing model, registered nurses worked at an advanced level/applied advanced practice nursing following in-house-training. Senior orthopedic specialists evaluated the diagnostic and treatment accuracy in both models. Data were collected in a tool developed for this study, from May to October 2019. Results: In total, 335 cases were included, of which 167 (49.9%) were assessed and treated in the nursing model. Overall, correct diagnosis was found in 97.3% ( n = 326) of the cases, and correct treatment was found in 91.3% ( n = 306) of the cases. In comparison of missed diagnosis between advanced practice nurse and the standard (physician-led) care model showed inconclusive results (risk ratio: 0.29, 95% CI: 0.06–1.36). In comparison of treatment outcomes, the results showed that the advanced practice nursing model was non-inferior (risk ratio: 0.45, 95% CI: 0.21–0.97). Conclusion: Advanced practice nursing care models can be used to diagnose and treat minor orthopedic injuries without compromising quality of care. Further implementation of the advanced practice nurse care model is encouraged.